2017
DOI: 10.7717/peerj.2845
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of TV-based game platforms as an instrument to support the cognitive evaluation of senior adults at home

Abstract: IntroductionThe computing capabilities of state-of-the-art television sets and media centres may facilitate the introduction of computer-assisted evaluation at home. This approach would help to overcome the drawbacks of traditional pen-and-paper evaluations administered in clinical facilities, as they could be performed in a more comfortable environment, the subject’s home, and they would be more flexible for designing complex environments for the evaluation of neuropsychological constructs that are difficult … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, both models aim to study acceptance. Both TAM and UTAUT have been used excessively to explain the use of several digital health applications, such as data sharing systems [29] and assessment tools for cognitive functions [30].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both models aim to study acceptance. Both TAM and UTAUT have been used excessively to explain the use of several digital health applications, such as data sharing systems [29] and assessment tools for cognitive functions [30].…”
Section: Introductionmentioning
confidence: 99%
“…Usability analysis was based on a 5-point Likert scale questionnaire to facilitate statistical analysis, ranging from strongly disagree (1 point) to strongly agree (5 points). The questionnaire is based on the TAM—Technology Acceptance Model ( Lee, Kozar & Larsen, 2003 ), which is considered more flexible to be adapted to different population samples in general, and to senior adults ( Costa et al, 2017 ) in particular. TAM indicates that the attitude towards a given technological system is determined by two subjective variables; namely, perceived ease of use (which provides an indication about the extent that a given individual believes that a particular technological system is easy to use) and perceived usefulness (which refers to the extent that a given individual believes that, using a particular technological system, his or her performance would improve).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, regarding the initial methodological step to define solutions, gamification techniques were introduced due to the limitations of classical tests. In addition, a user-centered design methodology was applied and usability was considered as a design priority due to the target users’ profile ( Costa et al, 2017 ). Furthermore, being aware of the lack of psychometric maturity ( Valladares-Rodríguez et al, 2016 ) of the case studies found in the literature ( Plancher et al, 2012 ; Plancher et al, 2013 ; Sauzéon et al, 2015 ; Jebara et al, 2014 ), this aspect was instrumental to guide both the design and implementation processes.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the acceptance of TV-based game platforms and simple games as an remote cognitive evaluation instrument [10] shows a 43% user-friendliness towards TV as a platform compared to smartphones with 29% and PC with 24% (n = 21, 65-90 years old). 91% of all participants stated that the TV is a very easy to use device and 75% would use TV-based gaming services again.…”
Section: Related Workmentioning
confidence: 99%